Penerapan Standar Akuntansi Pemerintahan, Sistem Pengendalian Intern dan Kualitas Laporan Keuangan - Hani Siti Hanifah (Fakultas Ekonomi Universitas Garut, 2020)
This study aims to determine the effect of implementing government accounting standards and internal control systems on the quality of financial reports. Length of the Regional Financial and Asset Management Agency (BPKAD) Garut Regency. The population used as a sample is as many as 55 respondents. The research method is a quantitative method with data collection through literature, questionnaires, and interviews. While the data processing technique uses the SPSS version 21.0 statistical application. The results showed that simultaneously government accounting standards and internal control systems have an effect on the quality of financial reports.